Comment: Psoriasis Uncovered - Comorbid Conditions with Special Reference to Metabolic Syndrome - Manuel Valdebran (Our Dermatology Online, 2014)
The association of psoriasis with cardiovascular disease, in particular, has been subject of research for many years, however, inconclusive results were always obtained as cardiovascular disease risk factors could act as confounders. Recently the topic have caught more attention as better designed studies have been performed thus confirming its association. Among these studies, it is very interesting to cite the meta-analysis performed by Miller et al [1] where they revised 75 relevant articles including more than 500,000 cases and found that psoriasis was associated with cardiovascular disease, ischemic heart disease, peripheral vascular disease, atherosclerosis, diabetes, hypertension, dyslipidemia, obesity by body mass index and by abdominal fat and metabolic syndrome but not associated with cerebrovascular disease and cardiovascular mortality.